2022
DOI: 10.3389/fpsyg.2022.945709
|View full text |Cite
|
Sign up to set email alerts
|

Musical Activity During Life Is Associated With Multi-Domain Cognitive and Brain Benefits in Older Adults

Abstract: Regular musical activity as a complex multimodal lifestyle activity is proposed to be protective against age-related cognitive decline and Alzheimer’s disease. This cross-sectional study investigated the association and interplay between musical instrument playing during life, multi-domain cognitive abilities and brain morphology in older adults (OA) from the DZNE-Longitudinal Cognitive Impairment and Dementia Study (DELCODE) study. Participants reporting having played a musical instrument across three life pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 107 publications
1
16
0
Order By: Relevance
“…These findings and the ones by Okely et al 20 . support the theory that learning to play a musical instrument has lasting impacts on multiple aspects of cognition, including executive function and working memory 22,26,28,32,33 . The findings particularly point towards a greater benefit to working memory, but not to executive function, when musical engagement is continued into older age.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These findings and the ones by Okely et al 20 . support the theory that learning to play a musical instrument has lasting impacts on multiple aspects of cognition, including executive function and working memory 22,26,28,32,33 . The findings particularly point towards a greater benefit to working memory, but not to executive function, when musical engagement is continued into older age.…”
Section: Discussionsupporting
confidence: 70%
“…These findings and the ones by Okely et al 20 support the theory that learning to play a musical instrument has lasting impacts on multiple aspects of cognition, including executive function and working memory. 22,26,28,32,33 The findings particularly point towards a greater benefit to working memory, but not to executive function, when musical engagement is continued into older age. Many musicians that took part in this study played the keyboard, which has previously been associated with better executive function and a greater activity among the pre-frontal and mid-central regions of the brain 34.…”
Section: Discussionmentioning
confidence: 88%
“…where musicians were found to have better visuospatial abilities among other cognitive abilities such as language, working memory, and executive functioning. [ 23 ] A notable point in our study is that the musicians were all Carnatic singers, and it has been evidenced that Carnatic music improves spatial reasoning by activating several limbic pathways that function through cortical networks. [ 24 ] Anaya et al ., have also suggested that musicians are able to learn and reproduce visuospatial information better than non-musicians.…”
Section: Discussionmentioning
confidence: 93%
“…In this cross-sectional study, we aimed to investigate to what extent self-reported playing of a musical instrument in early, middle, and late life stages (subsequently termed “lifetime musical activity”) might be related to RSFC within the FPN, DMN, SAL networks in cognitively unimpaired OA. As mentioned above, previous studies have shown that neural correlates associated with musical activity/experience in OA partially overlap with these higher-order brain networks [ 6 , 17 , 21 ]. We therefore addressed the hypothesis that participation in this multimodal lifestyle activity relates to increased RSFC in the triple networks.…”
Section: Introductionmentioning
confidence: 94%
“…Playing a musical instrument necessitates the activation and integration of multimodal motor, sensory, cognitive and emotional processes, which may help to preserve neural function in distributed brain networks into older age. Studies in cognitively unimpaired OA have shown that greater musical activity/experience is associated with greater neural resources or neural capacities in distant brain regions including higher-order frontal, temporal, and/or parietal areas [ 6 , 17 ]. This aligns with findings in young to middle-aged musicians, showing greater functional and/or structural connectivity within (but not limited to) frontal-temporal-parietal brain networks compared to control participants [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%